Exposing residual catalyst in a carbon nanotube sponge. Issue 51 (9th May 2016) - Yang, Liusi; Yang, Yanbing; Zhao, Xiulan; Zou, Mingchu; Wu, Shiting; Zhao, Ruo; Wang, Chunhui; Xu, Wenjing; Li, Yan; Cao, Anyuan
Abstract : Exposing residual catalyst in CNT sponges has potential applications as porous catalyst substrate and supercapacitor electrodes. Abstract : Carbon nanotubes (CNTs) are grown from metal catalysts; after growth, residual catalyst particles are usually encapsulated within the tube cavities and are difficult to remove. Here, we directly expose controlled amounts of Fe catalyst from a bulk CNT sponge by thermal annealing at mild temperature, and produce uniformly dispersed Fe2 O3 nanoparticles grafted onto CNTs throughout the sponge. Those exposed catalyst particles remain active and can be used to synthesize CNTs again. The resulting CNT–Fe2 O3 composite sponges, which possess a highly porous and conductive network, also serve as freestanding supercapacitor electrodes with significantly enhanced specific capacitance than original CNT sponges. Our results indicate that residual metal catalysts, widely present in CNT-based materials, can be reactivated and utilized for applications in catalysis and energy areas.